Exploring the Poles - Cullen, Derek; Murray-Robertson, John. (Needham, Mass. : Schoolhouse Press, 1988)
Describes journeys to the polar regions and the people who risked their lives to reach the coldest places on earth.
Includes index.
5.2
5-8
Keywords: Explorers; Explorers -- History; Voyages and travels -- History; Polar regions -- Discovery and exploration; Polar regions -- Discovery and exploration; Polar regions